High prevalence of betanodavirus barfin flounder nervous necrosis virus as well as red‐spotted grouper nervous necrosis virus genotype in shellfish. Issue 2 (13th October 2017) - Kim, Y C; Kwon, W J; Kim, M S; Kim, K I; Min, J G; Jeong, H D
Abstract: Using two serially executed PCRs, the discriminative multiplex two‐step RT‐PCR (DMT‐2 RT‐PCR) following the detection seminested two‐step RT‐PCR (DSN‐2 RT‐PCR), we found a high frequency presence of BFNNV genotype as well as RGNNV in various domestic and imported shellfish. This was definitely different from the previous reports of outbreaks and asymptomatic infection only by the RGNNV genotype in cultured finfish in Korea. Cultivation of NNV entrapped in shellfish was performed successfully by a blind passage. Thus, in an attempt to elucidate the epidemiology of betanodavirus, experiments conducted on 969 shellfish samples concluded that (i) distribution of NNV genotype, especially BFNNV, in shellfish is clearly different from that found in finfish of the world; (ii) unlike RGNNV, which showed a high rate in summer, BFNNV showed no seasonal variation and this result suggests BFNNVs in the marine environment remain fairly constant throughout the year; and (iii) the entrapped virus in shellfish was alive and culturable in vitro. These results are the first report of high level prevalence of in vitro culturable NNV in shellfish, for both BFNNV and RGNNV, which may present a potential risk in transmitting nodaviruses to host species in a marine environment.